How can android-based trigonometry learning improve the math learning process? - Hidayat, Wahyu; Rohaeti, Euis Eti; Hamidah, Ida; Putri, Ratu Ilma Indra (Frontiers in Education, 2023)
Using ICT-based interactive learning media is a learning method that strongly supports the teaching and learning process for students and teachers during the COVID-19 pandemic. This ICT-based learning media must be easily accessible to teachers and students, and one of the interactive media that is easily accessible is android-based learning media. This development research aims to design android-based learning media on valid trigonometric material and improve students’ mathematical critical thinking skills. This development research using the ADDIE model took 121 Ipeople consisting of expert validators, user (teacher), and students. The expert validators consisted of one mathematics education material expert and one ICT expert. Meanwhile, user represented by one mathematics teacher were involved in validating the use of the media design. In addition, there were participants from among students, which included 118 class X high school students throughout the Province of West Java, Indonesia, who took part in a limited trial phase of 20 people, an extensive trial of 50 people, and a product trial of 48 people. A sample of 118 students came from high school in the medium cluster. So, the reason for taking the sample represents the condition of students both on the island of Java and in Indonesia. The results showed that the developed android-based learning media was valid and could be used without revision with a combined percentage of 87.33%, with details of material experts at 84%, media experts at 92%, and validation by mathematics teachers at 86%. The results of the practicality test on students of 81% showed that the Android-based learning media design had a strong response, so the learning media made were very practical to use. The product test results show that the achievement of mathematical critical thinking skills of students who learn to use android-based learning media is better than those who learn not to use android-based learning media.